DINAMIKA SOSIAL PERAN GURU SEBAGAI AGEN PERUBAHAN LINTAS BUDAYA - Siti Arah Suniyah; Ahmadin; Ibrahim (LPPM Universitas Muhammadiyah Muara Bungo, 2026)
ABSTRACT The purpose of this study is to analyze the dynamics of teachers’ roles in the implementation of the Merdeka Curriculum and to identify transformative efforts undertaken by teachers in responding to emerging challenges in contemporary educational practice. This research employs a qualitative method with a library research approach, in which data were gathered from academic books, indexed journals, official reports, and relevant scholarly publications, and subsequently analyzed using content analysis techniques. The findings indicate that the primary dynamics in implementing the Merdeka Curriculum include unequal levels of teacher understanding regarding the new learning paradigm, limited availability of media to support the Pancasila Student Profile Project (P5), and the rapid development of educational technology that is not accompanied by sufficient collaborative spaces for teachers. These conditions contribute to uneven learning quality, difficulties in carrying out project-based learning, and an increased adaptive burden for teachers. The study also identifies several transformative efforts, including strengthening teachers’ professional literacy, developing innovative and contextual learning media, and expanding community-based collaborative networks. In this context, BASAsulsel Wiki serves as a collaborative ecosystem that provides digital learning resources, facilitates cross-sector dialogue through Youth Conferences, and promotes public participation through Wikithon initiatives addressing educational and social issues. This study underscores the importance of multi-stakeholder collaboration in supporting educational transformation and highlights the need for adaptive ecosystems to foster learning that is innovative, inclusive, and socially responsive. Keywords: Teacher Roles, Merdeka Curriculum, Educational Collaboration